Konsep Pengaturan Perjanjian Kerja Waktu Tertentu (PKWT) Berdasarkan Prinsip Keadilan Proporsional - Triasmono, Hari; Warka, Made; Setyaji, Sri; Hufron, Hufron (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the regulation of Fixed-Term Employment Agreements (PKWT) based on the principle of proportional justice in the Indonesian labor law system. This principle emphasizes the importance of a balance between the rights of employers to business flexibility and the rights of workers to protection and job security. This study uses a normative legal method with a statutory, conceptual, philosophical, historical approach, as well as a case and comparative approach. The primary legal materials analyzed include the Employment Law, the Job Creation Law, and the Constitutional Court Decision Number 168/PUU-XXI/2023. The results of the study show that changes to the regulation of PKWT through the Job Creation Law, especially the elimination of the maximum duration limit for extension, have created legal uncertainty for workers and opened up opportunities for abuse by employers. PKWT that is not strictly limited has the potential to harm workers, especially in terms of compensation and social security rights. Current regulations tend to favor employer flexibility, so there needs to be a rearrangement that prioritizes the principle of proportional justice. This justice must be reflected in the limitation of the use of PKWT for work that is truly temporary, the provision of adequate compensation, and strict supervision by the state. Theoretically, this finding confirms that employment law must be based on social justice that places humans at the center of policy, not merely objects of the labor market.